Synthesis and Separation of L-Trytophan Oligo-Peptides Assisted by Phosphorus Oxychloride - MA, LI; ZHAO, DONG-XIN; REN, HAI-PING; LU, KUI; ZHAO, YU-FEN (Asian Journal of Chemistry, 2010)
With the assistance of inorganic phosphorus, a-amino acids could self-assemble into a series of oligopeptides, so it could provide a new route to synthesize peptides. In this paper, the self-assembly reaction of L-trytophan mediated by phosphorus oxychloride was monitored by using ESI-MS. The proper condition of the self-assembly reaction of L-Try was reported. The reaction products were purified by RP-HPLC and the fragmentation pathway for L-Try oligo-peptides were analyzed by using ESI-MS/MS.